Indonesia’s Oil Palm Bioenergy Sustainability Assessment System using Indonesian Bioenergy Sustainability Indicators (IBSI) - Retdiyano Aliviar S; Yandra Arkeman; Erliza Hambali (International Journal of Engineering and Management Research, 2019)
Palm oil has potential to produce renewable energy bioenergy or often called bioenergy. Bioenergy from palm oil is priority government to make sustainable industry. Based on literature a basic principle of sustainability are: 1) Social, 2) Economic & 3) Environment. This research was conducted in Indonesia, where based on several palm oil company in Indonesia. The main purpose of the research is obtain system of bioenergy sustainability assessment in Indonesia which can be reference for sustainability level of bioenergy from palm oil. The intermediate objective to achive the main objective are: 1) Identification of the influence indicators to realize the sustainability of palm oil bioenergy, 2) Design a model for assessing the sustainability of palm oil bioenergy in Indonesia, 3) Analyze the level of sustainability of bioenergy in Indonesia with model system was already built. The methods used in this research to asses sustainability of bioenergy in Indonesia is Fuzzy Inference System (FIS). The result showed the level of oil palm bioenergy sustainability has score 61.7 for environment indicator, 50.1 for economic indicator, and 50.9 for social indicator. Overall, the level of bioenergy sustainability is 61.7, it means the sustainability level in Indonesia quite sustainable with confidance level is 80.6%, most sustainable with confidance level is 0%, and unsustainable with confidance 19.4%.